Use of reverse engineering method in verification of virtual prototypes - Winkler, Teodor; Tokarczyk, Jarosław; Bojara, Szczepan (Computer Assisted Methods in Engineering and Science, 2008)
The prototypes of Falling-Object Protective Structures (FOPS), which are used in self-propelled mining machines, undergo obligatory laboratory strength tests. The stand tests should be preceded with virtual prototyping of computer models to reduce the number of prototypes to an indispensable minimum. The Finite Element Method was used for the virtual prototyping. At the same time, after tests, the real protective structure was transformed by the Reverse Engineering method into a computer model. The deformations were compared on both models, at the same cross sections. The anthropometric model of operator was placed inside the reconstructed model.